Different drummers : military culture and its discontents - Tuleja, Tad, 1944- (University Press of Colorado e-book collection., 2020)
"Explores the disjunction between organizational solidarity and individual pushback in military organizations, examining how members of the armed forces express ambivalent or conflicted attitudes about their service. The volume focuses on psychological "discontent" within loyal opposition, considering examples of creative insubordination and analyzing 'oppositional positioning'"--